Withholding versus withdrawing treatment: artificial nutrition and hydration as a model. Issue 3 (September 2016) - Somers, Emma; Grey, Carl; Satkoske, Valerie
Abstract : Purpose of review: This article explores various cultural perspectives of withholding and withdrawing of life-sustaining treatment utilizing a case involving artificial nutrition and hydration (ANH) to guide ethical discussion. Recent findings: In the United States, there is a general consensus in the medical, ethical, and legal communities that the withholding and withdrawing of life-sustaining treatment are morally equivalent at the end of life. Despite this consensus, the withdrawal of treatment is still emotionally difficult, particularly with ANH. Recent literature challenges the evidence base that feeding tubes for people with advanced dementia lead to significant harm. In light of these new findings, we will reconsider end-of-life decision making that concerns ANH to determine whether these new findings undermine previous ethical arguments and to consider how to best educate and support patients and families during the decision-making process. Summary: Despite many believing that there is no ethical, medical, or moral difference between withholding and withdrawing of life-sustaining treatment, there is no denying it is emotionally taxing, particularly withdrawal of ANH. Upholding the patient's values during high-quality shared decision making, facilitating rapport, and utilizing time limited trials will help, even when treatment is considered medically ineffective.